Foreseen Demands for Up-and-coming Science Communicators and Recommendations for Science Communication Training Programs - TaylorAnn Washburn; Ch'Ree Essary; Erica Irlbeck; Courtney Gibson; Cindy Akers (Journal of Applied Communications, 2022)
Citizens interact with science on a daily basis, yet their understanding and opinions of scientific issues are formed with little scientific information. Science communication literature has called for scientists to take a more active role in engaging with the public through science communication efforts. However, scientists face demands and challenges that dissuade or prevent them from engaging in genuine communication efforts with a lay audience, including a lack of training. There has been an identified need for increased training programs for science communicators and students, but only a small number of programs currently exist. The purpose of this study was to identify demands faced by scientists who participate in communication practice in agricultural disciplines at Texas Tech University and to develop foundations for future science communications training curriculum at the college and/or university level. This descriptive, qualitative study consisted of semi-structured, in-depth interviews with 10 scientists at Texas Tech University who were identified as sought after for a variety of media interviews and communication efforts, and a criterion sampling strategy was used to identify “sought-after” communicators. The results of this study found that major demands faced by scientists include time constraints and academic value, and those demands inhibit genuine science communication efforts. Finally, recommendations regarding pedagogical foundations and subject matter content were developed for implementation in future science communication coursework at Texas Tech University.
Keywords: science communication; curriculum research framework; constructivism communication theory; higher education curriculum